Guide to bridge hydraulics - Neill, C. R. 1926- (Thomas Telford, 2004)
For most people, water under the bridge is something to shrug off and forget, but civil engineers cannot afford to be quite so cavalier about it. Members of a Transport Association of Canada project committee consider basic hydraulic considerations hydrological estimates; waterway design and analysis; scour protection and channel control; and hydr.
Keywords: Bridges -- Design and construction.; Hydraulics.; elektronické knihy; electronic books